A Tale of Two Kewangs: A comparative study of traditional institutions and their effect on conservation in Maluku - Karno Batiran; Ishak Salim (Forestry Faculty, Universitas Hasanuddin, 2020)
This study explains how kewang, a traditional institution that deals with social affairs and natural resource management, maintains traditional ecological knowledge and practices in Maluku. This study focuses on two comparative villages (negeri): Haruku and South Buano. The study adopts a historically situated new institutionalism approach to analyzing the dynamic developments of kewang and how it affects community members in the context of conservation and natural resource management of the petuanan customary areas of the two negeri. By examining institutional change including history, ideology, organization and authority of kewang with other institutional forms such as soa, government, church, and NGOs the study shows the path-dependence of the two respective kewangs. In Haruku, the kewang has long stayed intact because the institution is still practiced as a cultural principle, maintaining itself through the tradition-based leadership succession mechanisms and by continuing to carry out its functions, as well as pursuing innovations within kewang education for future generations. In South Buano however, due to the long absence of a kewang, efforts at revival show the strong influence of rational choice thinking principles, dependent on the formal authority of the negeri government. The study concludes that historical junctures shape the role and authority of kewangs in performing natural resource functions, and which can have longnstanding generational impacts on conservation possibilities. Meanwhile, kewang also rely on both its continued endogenous acceptance among local community members, and depend on its relations with other key institutions in society.